ANALISIS PENTINGNYA MEDIA DALAM PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR IPA DI SEKOLAH DASAR - Evi Hikma Setyarini; Alif Mudiono; Candra Utama (LPPM Institut Pendidikan Nusantara Global, 2022)
This study aims to review the use of learning media to improve science learning outcomes in elementary schools. While the method used in this study is the method of meta-analysis. This research begins by looking for relevant topics to make it easier for writers to collect data. The necessary data can be obtained by searching online journals through Google Academia with the keywords Learning Media, Improving Learning Outcomes, Natural Sciences, Elementary Schools. From the results of the search conducted, it was obtained more than ten articles but only 6 articles were relevant to use. Various kinds of relevant data that have been obtained are reprocessed using quantitative methods. Based on the results of the study of the use of media in learning, it is proven that it can improve student learning outcomes at a minimum of 43% and a maximum of 91%. The use of instructional media greatly influences student learning outcomes in science learning content in elementary schools. In addition to influencing learning outcomes, students also have different new experiences in each learning process using media. This activity can also improve students' ability to understand subject matter easily through the use of media during the learning process.